Biomechanical effects of sensorimotor orthoses in adults with Charcot–Marie–Tooth disease. (August 2016) - Wegener, Caleb; Wegener, Katrin; Smith, Richard; Schott, Karl-Heinz; Burns, Joshua
Background: Charcot–Marie–Tooth disease is an inherited neuropathy causing progressive weakness, foot deformity and difficulty walking. Clinical anecdotes suggest orthoses designed on the 'sensorimotor' paradigm are beneficial for improving gait in Charcot–Marie–Tooth disease. Objectives: Investigate the effect of sensorimotor orthoses on in-shoe and lower limb biomechanics in adults with Charcot–Marie–Tooth disease. Study design: Randomised, repeated-measures, exploratory study. Methods: Eight males and two females with Charcot–Marie–Tooth disease aged 31–68 years fitted with pedorthic shoes and custom-made sensorimotor orthoses were randomly tested at baseline and after 4 weeks of adaptation. In-shoe three-dimensional multi-segment foot and lower limb kinematics and kinetics were collected as were plantar pressures, electromyography and self-reported comfort, stability, cushioning and preference. Results: Compared to the shoe only condition, sensorimotor orthoses increased midfoot eversion and plantarflexion, increased ankle eversion and produced small but significant changes at the knee and hip indicating increased internal rotation. The orthoses increased medial ground reaction forces and increased pressure at the heel, midfoot and toes. There were minimal effects on electromyography. The sensorimotor orthoses were rated higher for comfort, cushioning, stability and preference. Conclusion: Sensorimotor orthoses produced changes in kinematic, kinetic and pressure variables in adults with Charcot–Marie–Tooth disease and were regarded as more comfortable, cushioned and stable during walking. Clinical relevance: In this study, the walking ability of patients with Charcot–Marie–Tooth disease improved with the use of foot orthoses designed according to the sensorimotor paradigm. However, the mechanism of action appears to be primarily mechanical in origin. Randomised controlled trials are necessary to evaluate the long-term patient-reported outcomes of sensorimotor orthoses.